(untitled) (Minerva, 2019)
This paper proposes to analyse the adultery and seizure passages in the Greek Novel. Although these offenses are framed in the literary context, they fit to the real crimes in regard to their definitions and their punishments. In the romance, the moicheia is already an offense against the husband-wife relation and the seizure is the way to have any sexual intercourse with a woman or to get married to one. The different periods and maybe the villages that the authors belong to, would explain several mentioned penalties, mainly those punishing the adulteress, which were more and more severe. These differences evidence the romance as a literary genre where the greek, roman and judaic elements are mixed.